2018
DOI: 10.1002/ags3.12200
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative globulin‐to‐albumin ratio predicts outcome after curative resection in patients with gastric cancer

Abstract: AimThe globulin‐to‐albumin ratio (GAR) is useful for prognostication of patients with various cancers. However, the significance of GAR in gastric cancer (GC) remains unclear. Our purpose was to investigate the relationship between the GAR and outcome after curative resection in GC patients.MethodsThree‐hundred and seventy‐six patients who had undergone curative resection for GC were retrospectively reviewed. Univariate and multivariate analyses using the Cox proportional hazard model were performed to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Globulin's involvement in chronic inflammation was observed via elevated levels associated with inflammatory responses and immunosuppression (18). High serum levels of Globulin (GLB) resulted in the poor prognosis of several cancers (19,20). An increase in CRP has been reported in many cancer cases, which reflects the inflammatory and immune response against tumor cells of the human body (21).…”
Section: Discussionmentioning
confidence: 99%
“…Globulin's involvement in chronic inflammation was observed via elevated levels associated with inflammatory responses and immunosuppression (18). High serum levels of Globulin (GLB) resulted in the poor prognosis of several cancers (19,20). An increase in CRP has been reported in many cancer cases, which reflects the inflammatory and immune response against tumor cells of the human body (21).…”
Section: Discussionmentioning
confidence: 99%
“…The Albumin-Globulin ratio increased significantly following the bariatric surgery, indicating a rise in albumin in plasma. A study done to observe if Globulin -Albumin ratio is a good predictor for gastric carcinoma following curative resection noted that a low Globulin -Albumin ratio pointed towards a good outcome 70 . They suggested that a raised globulin level in serum reflects tumor progression and antitumor immunity suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition, such as obesity (a state of chronic inflammation), causes albumin production suppression 72,73 . Since bariatric surgery promotes weight loss and improved BMI and reduces inflammation, there may be an improvement in the Albumin-Globulin ratio 70,74,75 . Also, following bariatric surgery, toll-like receptors (TLR-2 and TLR-4) expression, nuclear factor kappa β (inflammatory transcription factor), matrix metallopeptidase, and C-reactive protein decrease leading to lowering of systemic inflammation 76,77 .…”
Section: Discussionmentioning
confidence: 99%
“…NLR and PLR were set at 4 and 180 respectively, according to the previous description and practical situation. 18,25 The F-NLR-PLR score was calculated based on each cutoff value of plasma fibrinogen level, NLR and PLR counts. High plasma fibrinogen level (!4 g/L) was defined as 1, low plasma fibrinogen level (<4 g/L) was calculated as 0.…”
Section: Evaluation Standardmentioning
confidence: 99%
“…Some previous studies mentioned the association between the outcomes and these pretherapeutic inflammatory markers in several malignant tumors and indicated the significance in predicting the prognosis of various malignant tumors. [16][17][18][19] Recent research also found that the combination of these markers has prognostic values. 20,21 Moreover, the latest study demonstrated that high NLR was an unfavor-able predictor of prognosis for older adults with high-grade glioma.…”
Section: Introductionmentioning
confidence: 99%